Efficacy and safety of dual antiplatelet therapy in the elderly for stroke prevention: a subgroup analysis of the CHANCE-2 trial - Liping Liu; Yongjun Wang; Yilong Wang; Zixiao Li; Xingquan Zhao; Jing Jing; Philip M Bath; Hao Li; Xia Meng; Anxin Wang; Yong Jiang; Xinmiao Zhang; et al. (Stroke and Vascular Neurology)
Objectives Evidence of the optimal antiplatelet therapy for elderly patients who had a stroke is limited, especially those elder than 80 years. This study aimed to explore the efficacy and safety of dual antiplatelet therapy (DAPT) in old-old patients compared with younger patients in the ticagrelor or Clopidogrel with aspirin in High-risk patients with Acute Non-disabling Cerebrovascular Events-II (CHANCE-2) trial.Methods CHANCE-2 was a randomised, double-blind, placebo-controlled trial in China involving patients with high-risk transient ischaemic attack or minor stroke with CYP2C19 loss-of-function alleles. In our substudy, all enrolled patients were stratified by age: old-old (≥80 years), young-old (65–80 years) and younger (<65 years). The primary outcomes were stroke recurrence and moderate to severe bleeding within 90 days, respectively.Results Of all the 6412 patients, 406 (6.3%) were old-old, 2755 (43.0%) were young-old and 3251 (50.7%) were younger. Old-old patients were associated with higher composite vascular events (HR 1.41, 95% CI 1.00 to 1.98, p=0.048), disabling stroke (OR 2.43, 95% CI 1.52 to 3.88, p=0.0002), severe or moderate bleeding (HR 8.40, 95% CI 1.95 to 36.21, p=0.004) and mortality (HR 7.56, 95% CI 2.23 to 25.70, p=0.001) within 90 days. Ticagrelor-aspirin group was associated with lower risks of stroke recurrence within 90 days in younger patients (HR 0.68, 95% CI 0.51 to 0.91, p=0.008), which was no differences in old-old patients.Conclusion Elderly patients aged over 80 in CHANCE-2 trial had higher risks of composite vascular events, disabling stroke, severe or moderate bleeding and mortality within 90 days. Genotype-guided DAPT might not be as effective in old-old patients as in younger ones.Trial registration number NCT04078737.